2006
DOI: 10.1007/s00261-005-0048-7
|View full text |Cite
|
Sign up to set email alerts
|

Aneurysm of the inferior vena cava: case report

Abstract: Venous aneurysms are uncommon. Despite their infrequency, venous aneurysms can present with significant clinical complications such as thrombosis, pulmonary embolism, and death. In this report, we present the case of a thrombosed inferior vena cava aneurysm discovered in a 16-year-old male who had deep vein thrombosis of the right lower extremity. Thrombosis of the inferior vena cava is uncommon in the pediatric population. Therefore, congenital abnormalities such as an inferior vena cava aneurysm should be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
0
22
0
Order By: Relevance
“…Trauma or inflammatory processes have also been proposed as inciting factors of acquired aneurysms. 3 Etiology is unknown for most of them, but some authors have suggested an embryological or congenital origin, given their occasional association with other congenital anomalies. 4 In this case, the young age at presentation, absence of previous trauma, or other conditions support this hypothesis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Trauma or inflammatory processes have also been proposed as inciting factors of acquired aneurysms. 3 Etiology is unknown for most of them, but some authors have suggested an embryological or congenital origin, given their occasional association with other congenital anomalies. 4 In this case, the young age at presentation, absence of previous trauma, or other conditions support this hypothesis.…”
Section: Discussionmentioning
confidence: 97%
“…It was not possible to establish whether the aneurysm was sacular or fusiform because of the massive bleeding that occurred during surgery. [3][4][5] Although arterial aneurysmal dilatations represent a well-recognized clinical entity, these formations rarely appear in the venous territory. Aneurysms involving the IVC are extremely uncommon with <30 reported cases, and exceptionally described in children.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8 This approach also allows for thrombolytic therapy in patients presenting with lower extremity swelling and an IVC thrombus. 9 Observation of asymptomatic aneurysms, regardless of location, is an appropriate treatment option and should not be forgotten. In addition to the success of nonoperative management with our patient, Woo et al 10 describe a 5-cm pararenal IVC aneurysm that was successfully treated expectantly with serial CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Thus, for the current case, the definitive management would have been surgical resection of the aneurysm or thrombolysis followed with systemic anticoagulation. [12] Due to unfavorable circumstances of the patient, surgical intervention was deferred and patient was counseled about medical treatment along with proper domiciliary care including physiotherapy. Patient was also informed about thrombotic complications, pulmonary embolism, and sudden death as a consequence of non-operative management.…”
Section: Discussionmentioning
confidence: 99%